Erectile Dysfunction and Sexual Coercion: The Role of Sperm Competition Risk. - Vance, Gavin; Zeigler-Hill, Virgil; Shackelford, Todd K. (Archives of Sexual Behavior, 2022)
Erectile dysfunction (ED) has been shown to be associated with several negative aspects of intimate relationships. Our goal for the present research was to examine whether ED was associated with men's use of sexual coercion in their intimate relationships (which may include the use of physical coercion, psychological manipulation, or emotional manipulation to gain sexual access) and if perceived sperm competition risk (i.e., perceived risk of partner infidelity, which may place a man's sperm into competition with sperm from another man) played a role in this association. These associations were examined in Study 1 using self-reports provided by men (N = 202) who had a mean age of 30.48 years (SD = 5.03) and were recruited through Amazon's Mechanical Turk (MTurk). ED was found to have a large positive association with sexual coercion. However, men's self-reports did not provide support for sperm competition risk moderating the association between ED and sexual coercion, but an exploratory analysis revealed that sperm competition risk mediated this association. We attempted to replicate and extend these results in Study 2 by using partner-reports provided by women (N = 151) who had a mean age of 30.41 years (SD = 4.77) and were recruited through MTurk. Women's partner-reports provided support for sperm competition risk moderating the association between ED and sexual coercion. In addition, an exploratory analysis found that sperm competition risk also mediated the association between ED and sexual coercion, similar to Study 1. Discussion explores the implications of these results for understanding the role that sperm competition risk may play in the connection between ED and sexual coercion.